HIV infection and risk for incident pulmonary diseases in the combination antiretroviral therapy era. - Crothers, Kristina; Huang, Laurence; Goulet, Joseph L; Goetz, Matthew Bidwell; Brown, Sheldon T; Rodriguez-Barradas, Maria C; Oursler, Krisann K; Rimland, David; Gibert, Cynthia L; Butt, Adeel A; Justice, Amy C (American journal of respiratory and critical care medicine, 2011)
In aging HIV-infected populations comorbid diseases are important determinants of morbidity and mortality. Pulmonary diseases have not been systematically assessed in the combination antiretroviral therapy (ART) era.
Keywords: Adult; Antiretroviral Therapy, Highly Active; Asthma; Cohort Studies; Female; HIV Infections; Humans; Hypertension, Pulmonary; Incidence; Lung Diseases; Lung Neoplasms; Male; Middle Aged; Poisson Distribution; Pulmonary Disease, Chronic Obstructive; Pulmonary Fibrosis; Regression Analysis; Risk Factors; United States